2022
DOI: 10.1177/09603271221102504
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio versus platelet-to-lymphocyte ratio in predicting clinical outcomes in acute methanol poisoning

Abstract: Acute methanol poisoning is a global health concern. This study was designed to compare the prognostic roles of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and their combination in the prediction of clinical outcomes in methanol-intoxicated patients as well as to evaluate their associations with all initial patients’ characteristics. We conducted a cross-sectional study among methanol-intoxicated patients. A total of 109 patients were enrolled in the study. Thirty-four (31%) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…However, in a study evaluating 109 methanol poisoning patients, the researchers noted that NLR was able to distinguish death and survival with high performance, but it was ineffective in predicting vision loss. 25 The researchers reported that the use of the platelet-to-lymphocyte ratio will provide better results than NLR in predicting permanent vision loss. 25 There are also studies reporting that the red blood cell distribution width value, which is one of the hemogram parameters, is statistically significantly higher in patients who died from methanol poisoning compared to those who survived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a study evaluating 109 methanol poisoning patients, the researchers noted that NLR was able to distinguish death and survival with high performance, but it was ineffective in predicting vision loss. 25 The researchers reported that the use of the platelet-to-lymphocyte ratio will provide better results than NLR in predicting permanent vision loss. 25 There are also studies reporting that the red blood cell distribution width value, which is one of the hemogram parameters, is statistically significantly higher in patients who died from methanol poisoning compared to those who survived.…”
Section: Discussionmentioning
confidence: 99%
“… 25 The researchers reported that the use of the platelet-to-lymphocyte ratio will provide better results than NLR in predicting permanent vision loss. 25 There are also studies reporting that the red blood cell distribution width value, which is one of the hemogram parameters, is statistically significantly higher in patients who died from methanol poisoning compared to those who survived. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Future research should focus on possible predictors of the risk of death from methanol poisoning. Abdelwahab et al, proposed to use the neutrophil-to-lymphocyte ratio and the platelet-tolymphocyte ratio as predictors for acute methanol poisoning [30]. Future research must focus on the early symptoms of methanol poisoning and carefully examine the changes in the body that occur immediately after ingestion.…”
Section: Discussionmentioning
confidence: 99%